Packaging with lower sperm concentrations improves post-thawing quality parameters of rooster semen - Esther Díaz Ruiz; Juan Vicente Delgado Bermejo; Francisco Javier Navas González; José Manuel León Jurado; Antonio González Ariza (Italian Journal of Animal Science)
Standardisation of the sperm cryopreservation technique in cockerels plays a key role, with sperm concentration being an important factor to determine. The present study aims to determine which sperm concentration provides the best post-thawing semen quality results. Semen was extracted from 16 males belonging to the Utrerana poultry breed, making a pool with the quality ejaculates for each day of semen extraction, totalling 27 replicates of which 15 were frozen at 500 x 106 spz/straw and 12 at 250 x 106 spz/straw. From each replicate, four samples are thawed to evaluate the following semen quality parameters: motility, morphology, membrane functionality (HOST), sperm viability, acrosome integrity, lipid peroxidation (LPO), reactive oxygen species (ROS), and glutathione. By means of a canonical discriminant analysis, it was determined that HOST (Lambda = 0.484, F = 113.193), straight-line velocity (VSL) (Lambda = 0.613, F = 66.963), straightness (STR) (Lambda = 0.697, F = 46.086), sperm viability (Lambda = 0.707, F = 43.860), and ROS (Lambda = 0.876, F = 15.073) were the variables that provided the most information. According to the descriptive statistics, there are better results when freezing at 250 x 106 spz/straw for HOST (70.391 vs. 50.620), STR (76.917 vs. 72.017), sperm viability (44.880 vs. 27.638), and ROS (1019.042 vs. 1139.350). On the contrary, the VSL variable showed more favourable values when increasing the concentration to 500 x 106 spz/straw (41.375 vs. 32.652). Thus, generally, we can conclude that a low freezing sperm concentration leads to better quality results in thawed rooster semen.